Energy studies on high yield container farming systems - Koh, Pei Xin (2015)
In consideration of the world forecast on population growth rate, food security, water and land being a finite source, intensifying urban farming through the establishment of vertical farming system in urban centers is the likely solution. The aim is to raise the production yield per square meter plot of land in land scare Singapore as a viable solution. Most of the studies had been done on the viability of vertical farming with consideration of plant growth rate and quality. However, the financial and energy consumption feasibility of vertical farming have not been established to determine whether such solutions are commercially viable and are able to grow produce at a realistic cost level. A detailed cost-benefit and energy-benefit analysis is yet to be made in order to support its advantage over the conventional traditional farming system. The objective of this project is to verify the viability of vertical farming system with LED supplementary light as compare to the conventional hydroponic farming system. The analysis is made from the basis of energy consumption, cost, plant growth quality and plant yield of the two farming systems. Lastly, this work further researched on the benefits and importance of vertical farming. In this experiment, the specimen used is the Butterhead lettuce procured from OH! Chin Huat hydroponic farm. Both traditional hydroponic and vertical farming systems’ set up were done in NIE greenhouse, using the hydroponic method- Nutrients Film Technique. The vertical farming approach was conducted in a ‘dark room’ condition (absence of sunlight). The plants were cultivated under five different colors of LED lights , which include Red(R), Blue(B), White(W), a combination of Red and Blue(RB)and a combination of red, blue and white(RBW). As for the traditional hydroponic farming system, the plants grow under sunlight without any supplementary light energy. The same measured parameters were applied for both approaches, which include energy consumption, plant growth rate, fresh weight, dry weight, chlorophyll contain and number of leaves. In conclusion, there are pros and cons for both methodologies. Results show that energy consumption of the five LED light contributes 90.12% of the total energy consumption of the vertical farming set-up. The plants grow under red/blue LED light has the best overall growth among all the LED lights. As to yield 1kg of Buttherhead lettuce via vertical farming system, it required 11 times more energy compare to conventional hydroponic farming system. Apart from that, vertical farming system has lower performance in terms of plant’s quality and growth rate. However, the number of lettuce plants that can be grown per square meter for a 3.9m height vertical farming system which is around 7 times more than conventional hydroponic farming system.